Analytical synthesis of the algorithm of the operator’s operation at the freckles frequency - Гученко, М. І. (Proceedings of National Aviation University (archive), 2002)
The problem of analytical synthesis of the algorithm of the operator’s operation on the frequency of the silica in the one-channel compensatory tracking system with a harmonic perturbation signal is considered. Examples of numerical modeling of the problem are given. Analytically found the amplitude of the third harmonic of the operator’s response